Implementasi Kebijakan dan Komunikasi Antar Organisasi dalam Optimalisasi Kelembagaan Dinas Perijinan dan Penananaman Modal - M. Widaningsih; Silvy Vebritha; Husni Muharam (Journal of Social and Policy Issues, 2022)
To improve the economic capacity of a region, one of which is by investing in accordance with the paradigm of Endogenous Development strategy, which is to harmonize natural forces with human resource strengths. However, we still encounter many problems when we are about to make this investment, one of the problems is related to licensing which is still very complicated, requires a very long and complicated bureaucratic route. This is what prompted the researchers to conduct research on what is the problem with the difficulty of the licensing process. The researcher conducted this research using a qualitative research method in which he analyzed data from interviews with informants involved in the investment. The results obtained in this study are that there is still a large gap between investment interest and investment realization, which is one of the reasons for the weakness in policy implementation and communication between organizations.